(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
In this article, when interpreted as a political concept and legal principle that regulates the relationship between religion and the state, the general and specific signs of secularism are given. Although secularism has political and philosophical underpinnings, it is essentially moral because it aims to provide people with a certain way of life and a way of life.